Fishes - Jongkar, Grinang; lee, nyanti; Nur Ezaimah, Idris; Hafida, Bolhen; Mustafa Kamal, Mohd Faizal; Cindy, Peter; Jacqleen, Mik; Ling, Teck Yee; Sim, Siong Fong (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
Within the natural state of freshwater ecosystem, high species richness of ichthyofauna is correlated with size of river, drainage pattern and habitat heterogeneity. The species-area relationship has been demonstrated in other large tropical river systems including Amazon River (~6,4000 km, ~2,716 species), Congo River (~4,700 km, ~1,200 species) and Mekong River (~4,320 km, ~1,200 species). The number of species of freshwater fish from Borneo has never been estimated, although the existence of large rivers such as Kapuas in West Kalimantan (~1,143 km), Barito in South Kalimantan (~900 km), Mahakam in East Kalimantan (~775 km), Kahayan in Central Kalimantan (~658 km), Rajang in Sarawak, East Malaysia.